Tumour associated endothelial cells: origin, characteristics and role in metastasis and anti-angiogenic resistance - Yao, Xinghong; Zeng, Ye (Frontiers in Physiology, 2023)
Tumour progression and metastasis remain the leading causes of cancer-related death worldwide. Tumour angiogenesis is essential for tumour progression. The vasculature surrounding tumours is not only a transport channel for nutrients, oxygen, and metabolites, but also a pathway for tumour cell metastasis. There is a close interaction between tumour cells and endothelial cells in the tumour microenvironment. Recent studies have shown that tumour-associated endothelial cells have different characteristics from normal vascular endothelial cells, play an important role in tumour progression and metastasis, and are expected to be a key target for cancer therapy. This article reviews the tissue and cellular origin of tumour-associated endothelial cells and analyses the characteristics of tumour-associated endothelial cells. Finally, it summarises the role of tumour-associated endothelial cells in tumour progression and metastasis and the prospects for their use in clinical antiangiogenic therapy.